Spinel peridotite, olivine websterite and the textural evolution of the Purang ophiolite complex, western Tibet. (1st October 2015) - Li, Xu-Ping; Chen, Hong-Kai; Wang, Ze-Li; Wang, Li-Jun; Yang, Jing-Sui; Robinson, Paul
Highlights: Ultramafic rocks of the Purang ophiolites are mantle peridotites with various degrees depletion. Textural and mineralogical evolutions of ultramafic rocks were preserved and studied in detail. Ultramafic rocks recorded multistage melting and melt/rock reaction processes. They may form in mid-ocean ridge or an evolved back-arc basin, and then were trapped in SSZ setting. Abstract: Spinel peridotite and associated olivine websterite form an ultramafic massif at the base of the Purang ophiolite complex of western Tibet. The spinel peridotites consist chiefly of harzburgites with lesser amounts of lherzolite and dunite. All of the peridotites are rich in MgO, but depleted in Al2 O3, CaO and TiO2 relative to primary mantle values, indicating depletion by several episodes of partial melting. The olivine websterite was probably generated from evolved melts that had reached olivine saturation and that reacted with the host harzburgite. The evolution of the Purang ultramafic rocks from lherzolite through harzburgite and dunite to olivine websterite, indicates multistage melting and melt/rock reaction processes. Decompression-related textures such as exsolution lamellae of clinopyroxene and spinel in orthopyroxene, melting and melt/rock reaction textures, such as embayed, flame-like grains of spinel and partial chain spinel textures are widespread in the ultramafic rocks. Impregnation textures are reflected by the presence of late intergranular and interstitial clinopyroxene and spinel in the harzburgite, dunite and olivine websterite. Mineral textures vary from lherzolite to harzburgite and dunite to olivine websterite, and equilibrium temperatures of corresponding mineralogical assemblage increase as the degree of melt metasomatism or melt–rock reaction increase. Chromer spinels in the lherzolite with Cr # s (100Cr/(Cr + Al) of 26–33 may have formed beneath a mid-ocean ridge system or in an evolved back-arc basin, whereas spinel in the harzburgite, which has Cr # s of 39–57, is thought to record both abyssal and supra-subduction zone processes. Dunite and olivine websterite containing Cr-spinel with Cr # s of 60–64 and 52–87, respectively, reflect melt–rock reaction in a supra-subduction zone environment. Plots of TiO2 vs Al2 O3 for spinel and Al2 O3, TiO2 and Cr # vs Mg # for orthopyroxenes of the Purang ophiolite also support these conclusions. The Purang spinel peridotites thus provide a good example of multistage melt extraction, as well as melt/rock and metasomatic reactions in an ophiolitic mantle sequence.